Efficacy and safety of switching from nevirapine immediate-release twice daily to nevirapine extended-release once daily in virologically suppressed HIV-infected patients: a retrospective cohort study in Taiwan - Chun-Yuan Lee; Hui-Min Chang; Calvin M Kunin; Susan Shin-Jung Lee; Yao-Shen Chen; Hung-Chin Tsai (BMC Infectious Diseases, 2017)
Abstract Background Whether the non-inferior efficacy and safety results of switching virologically suppressed HIV-1-infected patients from nevirapine immediate-release (NVP-IR) to NVP extended-release (NVP-XR) demonstrated in the TRANxITION study conducted in Europe and North America are also applicable to virologically suppressed HIV-infected Taiwanese patients remains unknown. We evaluated the comparative safety and efficacy of continuing NVP-IR versus switching to NVP-XR in virologically suppressed HIV-infected Taiwanese adults receiving combined antiretroviral therapy (cART) regimens. Methods We conducted a retrospective cohort study at Kaohsiung Veterans General Hospital from April 1, 2013, to March 31, 2015. Eighty-four virologically suppressed HIV-infected adults receiving NVP-IR cART were split into two groups: those continuing with NVP-IR (n = 49) and those being switched to NVP-XR (n = 35). Demographic characteristics, clinical variables, and laboratory findings were compared. Therapeutic drug monitoring of steady-state plasma NVP concentrations and genotype analysis of CYP2B6 516 were also performed in 22 participants. The primary endpoint was continued virological suppression at the end of the study. Secondary endpoints were time to loss of virological response and adverse events. Results During a mean follow-up of 18.4 months, the NVP-XR group demonstrated similar success at maintaining virological response compared with the NVP-IR group (82.9% vs. 85.7%; P = 0.72). Cox regression analysis indicated that there were no significant differences between NVP regimens for time to loss of virological response (hazard ratio: 0.940; P = 0.754). Furthermore, there were no significant differences in adverse events between these two groups. In the 22 participants, there was a non-significantly lower level of steady-state plasma NVP concentrations in the NVP-XR group than in NVP-IR recipients (5145.0 ng/mL vs. 6775.0 ng/mL; P = 0.267). The prevalence of CYP2B6 516 GT was 86.6%, and there was no significant difference in the distribution of CYP2B6 516 between these two groups. Conclusions We found that switching from NVP-IR to NVP-XR appeared to have similar safety and efficacy compared with continuing NVP-IR among virologically suppressed, HIV-infected Taiwanese patients. Our finding of higher Ctrough levels in both groups compared with other studies conducted in Caucasian populations and the high prevalence of CYP2B6 516 GT requires further investigation in a larger Taiwanese cohort.